2018
DOI: 10.1186/s40623-018-0829-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humidity and interlayer cations on the frictional strength of montmorillonite

Abstract: We developed a humidity control system in a biaxial friction testing machine to investigate the effect of relative humidity and interlayer cations on the frictional strength of montmorillonite. We carried out the frictional experiments on Na-and Ca-montmorillonite under controlled relative humidities (ca. 10, 30, 50, 70, and 90%) and at a constant temperature (95 °C). Our experimental results show that frictional strengths of both Na-and Ca-montmorillonite decrease systematically with increasing relative humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
(51 reference statements)
2
24
1
Order By: Relevance
“…Therefore, the water swelling law of the integrated montmorillonite matrix in mudstone can be indirectly characterised by determining the water content within it. density versus water content ( Figure 14) and compared with data calculated by Equation (2). The experimental results were found to be in good agreement with the calculated results for the hydration swelling model obtained above; therefore, its rationality was verified.…”
Section: Hydration Swelling Modelsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, the water swelling law of the integrated montmorillonite matrix in mudstone can be indirectly characterised by determining the water content within it. density versus water content ( Figure 14) and compared with data calculated by Equation (2). The experimental results were found to be in good agreement with the calculated results for the hydration swelling model obtained above; therefore, its rationality was verified.…”
Section: Hydration Swelling Modelsupporting
confidence: 78%
“…It is considered that the fitting equation (Equation 2) accurately describes the hydration swelling of integrated specimens with a goodness of fit of 0.96, and this accurately reflects the hydration swelling properties of integrated specimens: The relationship between the average density and w was linearly fitted and is shown in Figure 13. It is considered that the fitting equation (Equation 2) accurately describes the hydration swelling of integrated specimens with a goodness of fit of 0.96, and this accurately reflects the hydration swelling properties of integrated specimens: All the densities of integrated specimens obtained earlier were plotted within the space of density versus water content ( Figure 14) and compared with data calculated by Equation (2). The experimental results were found to be in good agreement with the calculated results for the hydration swelling model obtained above; therefore, its rationality was verified.…”
Section: Hydration Swelling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-direct shear tests of the cleavage planes of mica on two sliding planes were performed as in our previous studies ( 14 , 15 ) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…where μ is the frictional coefficient and C is the frictional cohesive strength. Frictional coefficients are similar for most investigated minerals (μ = 0.6-0.85; Byerlee 1978); however, recent laboratory data have shown that several clay minerals yield much lower coefficients (μ~0.1; Morrow et al 2000;Tetsuka et al 2018). In the present study, we used Byerlee's law to calculate the mechanical strength in the regions undergoing brittle deformation, but we also discuss the effect of clay minerals that reduce brittle strength at wet environment.…”
Section: Rheological Structuresmentioning
confidence: 91%